A Case Study of An Ergonomic Risk Assessment for Working Posture among Maintenance Workers - Abdol Rahman, Mohd Nasrull; Zhan Yek , Lay (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The purpose of ergonomics is to take advantage of human ability limits in order to implement an efficient and comfortable interface to use. When the worker is performing an improper posture, it may cause the worker to feel discomfort when doing the work and may lead to getting musculoskeletal disorders (MSD). According to past research, there is a relationship between impropper working posture and MSD. The objective of this study was to determine the relationship between Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA) and Entire Body Risk Assessment (ENBORA). CMDQ, RULA, REBA and ENBORA were conducted among 34 maintenance workers around Parit Raja, Johor. The selected maintenance workers were interviewed via CMDQ and RULA, REBA and ENBORA were conducted based on their working posture at the time of the interview. The data were analyzed and compared based on similar observed body parts. Among the respondents, lower back discomfort was most prevalent (70.59%), followed by right and left shoulders (58.82% and 55.88%, respectively) as well as right wrist (29.47%) and left wrist (55.88%). The mean RULA Score for the respondents was 4.76 (SD=1.37) which indicates a medium risk level. The mean REBA Score for the respondents was 7.41 (SD=2.26) which indicates the average REBA risk level was high. The mean value for the ENBORA Final Score was 33.56 (SD=11.98), indicating that the respondents overall have a negligible risk of getting MSD based on their working posture. The body parts compared in CMDQ, RULA, REBA and ENBORA were neck, upper arm, lower arm, wrist and trunk. Based on findings, ENBORA has the highest Pearson Correlation to CMDQ followed by RULA and REBA. In conclusion, the maintenance workers were found to be exposed in ergonomic risk factors (ERFs) and ergonomics improvement were needed in future.